Development of recombinant outer membrane proteins vaccine and its immunoprotective ability against Vibrio alginolyticus in hybrid grouper (Epinephelus fuscoguttatus Forsskal x Epinephelus lanceolatus Bloch) - Rosli, Nehlah (2016)
The productions of grouper may become restricted due to many constraints, including diseases. The most significant bacterial disease attacking groupers is vibriosis and its major causative agent is Vibrio alginolyticus. This study was conducted to develop recombinant cells vaccine containing antigenic OmpK and OmpW genes from V. alginolyticus by gene cloning and protein expression, and to evaluate the immune response and protection efficacy of hybrid grouper following exposure to virulent V. alginolyticus. The selected V. alginolyticus strain VA2 was first identified to confirm it as V. alginolyticus by phenotypic and genotypic characterization. In addition, the antigenicity analysis of the outer membrane proteins (OMPs) of V. alginolyticus strain VA2 was carried out. The OMPs were isolated and purified, followed by protein profiling using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and antigenicity analysis was done using Western blotting. The SDS-PAGE profiling revealed a mixture of major and minor protein bands. The 23 and 31 kDa protein bands, postulated to be the OmpW and OmpK proteins, respectively, were antigenic as shown by Western blot. The vaccine was constructed by purifying PCR products of OmpK and OmpW genes from V. alginolyticus, followed by transformation into cloning and expression hosts, Escherichia coli TOP10 and BL21(DE3), respectively. Sequencing analysis revealed that the full length of target genes OmpK and OmpW of V. alginolyticus strain VA2 were 846 and 642 bp, respectively. The sequences of the target genes were highly similar to published sequences of Vibrio species in GenBank. The multiple sequence alignment showed that their amino acid sequences were highly conserved between different Vibrio species. High numbers of antigenic sites were also predicted in the OmpK and OmpW protein sequences. Pilot expression was done for recombinant OmpK and OmpW to determine the optimum expression temperature and time, which were revealed to be 30°C for 10 h. The expressed target proteins were then detected by His-tag monoclonal antibody using SDS-PAGE and Western blotting, in which the presence of fusion proteins at 48.3 kDa and 40.3 kDa for OmpK and OmpW respectively, were confirmed. For vaccination, formalin killed whole-cell of V. alginolyticus strain VA2 was prepared at concentration of 1.59 x 107 and 8.3 x 107 CFU/ml for OmpK and OmpW respectively. Six groups of 150 hybrid groupers each, at approximately 30 g was acclimatized beforehand for two weeks. These six groups were for treatments of rOmpK, rOmpW, rOmpK+rOmpW, Eschericia coli only, PBS only and control without manipulation. Vaccination was done by intraperitoneal injection on day 0. Booster dose was given on day 14. On day 28, all fish were challenged with virulent strain of V. alginolyticus at concentration of 1 x 109 CFU/mL by intraperitoneal (IP) injection. Blood serum and gut samples were collected biweekly until week 10. The survival percentages were highest for OmpK+OmpW and OmpK vaccinated groups at 100%, followed by OmpW vaccinated group at 67%, PBS group at 12%, and E. coli group at 0%. Enzyme-linked immunosorbent assay (ELISA) analysis showed significant (p<0.05) antibody difference between vaccinated and non-vaccinated groups from week 2 to week 10. After booster dose, the antibody level of bivalent vaccine OmpK+OmpW was significantly higher (p<0.05) than other groups. However, it was not significantly different (p>0.05) than monovalent vaccine OmpK after challenge at week 4. Gut histology showed presence of gut-associated lymphoid tissue (GALT) in vaccinated groups only. This showed that while bivalent vaccine OmpK+OmpW is effective, monovalent vaccine OmpK alone is also strong enough to give protection to groupers against high concentration of virulent V. alginolyticus.